2017
DOI: 10.1103/physrevfluids.2.094801
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of rapidly rotating Rayleigh-Bénard convection to Ekman pumping

Abstract: The dependence of the heat transfer, as measured by the nondimensional Nusselt number N u, on Ekman pumping for rapidly rotating Rayleigh-Bénard convection in an infinite plane layer is examined for fluids with Prandtl number P r = 1. A joint effort utilizing simulations from the Composite Non-hydrostatic Quasi-Geostrophic model (CNH-QGM) and direct numerical simulations (DNS) of the incompressible fluid equations has mapped a wide range of the Rayleigh number Ra -Ekman number E parameter space within the geos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 19 publications
4
41
0
1
Order By: Relevance
“…This suggests the existence of a more complex 2‐D surface in Nu ( E , Ra ) parameter space (Kunnen et al, ; Stellmach et al, ). For E <10 −7 and Pr =1 fluids, Plumley et al () suggested that the surface can be expressed as Nu1false(1+Pfalse(Efalse)false)false(RaE4false/3false)3false/2 indicating the dissipation‐free scaling law is enhanced by Ekman pumping by the multiplicative prefactor (1+ P ( E )) where P ( E )≈5.97 E 1/8 was fit empirically with their numerical simulations, as shown in Figure b. This indicates a singular transition in the sense that its dependence on supercriticality has an inverse relationship with E ; that is, it is increasingly delayed and moves to infinity as E →0.…”
Section: Rbc With Rotationmentioning
confidence: 80%
See 4 more Smart Citations
“…This suggests the existence of a more complex 2‐D surface in Nu ( E , Ra ) parameter space (Kunnen et al, ; Stellmach et al, ). For E <10 −7 and Pr =1 fluids, Plumley et al () suggested that the surface can be expressed as Nu1false(1+Pfalse(Efalse)false)false(RaE4false/3false)3false/2 indicating the dissipation‐free scaling law is enhanced by Ekman pumping by the multiplicative prefactor (1+ P ( E )) where P ( E )≈5.97 E 1/8 was fit empirically with their numerical simulations, as shown in Figure b. This indicates a singular transition in the sense that its dependence on supercriticality has an inverse relationship with E ; that is, it is increasingly delayed and moves to infinity as E →0.…”
Section: Rbc With Rotationmentioning
confidence: 80%
“…Thus, scaling laws have been observed even at relatively low supercriticality. The asymptotic analysis and results showing convergence to scaling laws (Plumley et al, ) suggest that it is appropriate to benchmark theoretically deduced scalings with the numerical experimental results in the less supercritical, but accessible regime.…”
Section: Rbc With Rotationmentioning
confidence: 99%
See 3 more Smart Citations